Validation and reliability of the Malaysian English version of the psychosocial impact of dental aesthetics questionnaire for adolescents - Wan Hassan, W.N. (2016)
Background: The Malay version of the Psychosocial Impact of Dental Aesthetics Questionnaire (Malay PIDAQ) has been shown to be valid and reliable for use by Malaysian adolescents. In a multi-ethnicity country like Malaysia, some adolescents’ mother tongue may be influenced by their racial background and may not necessarily be proficient in the national Malay language. An instrument validated for one language only may not be able to capture the psychometric information from these adolescents. English is the second national language in Malaysia and is widely used as the lingua franca among Malaysians of different ethnicities. The aim of the study was to validate an English version of the PIDAQ adapted for use by Malaysian adolescents. Methods: The published English version of PIDAQ was pilot tested on 12- to 17-year-old adolescents, resulting in a few modifications to the 23 items to suit the Malaysian variety of English. The psychometric properties of the adapted English PIDAQ were tested on 393 adolescents who attended orthodontic practices and schools. Malocclusion was assessed using the Malocclusion Index, which is an aggregation of Perception of Occlusion Scale and the Aesthetic Component of the Index of Orthodontic Treatment Need by the subjects (MI-S) and investigators (MI-D). Data were analysed for internal consistency and age-associated invariance, discriminant and construct validities, reproducibility and floor and ceiling effects using AMOS v.20 and SPSS v.20. Results: Confirmatory factor analysis showed good fit statistics (comparative fit index = 0.900, root-mean-square error of approximation = 0.066). Internal consistency of all subscales in all age groups were adequate (Cronbach’s alpha = 0.72-0.85) while the reproducibility test was acceptable (intra-class correlations = 0.59-0.78). For all PIDAQ subscales, the MI-S and MI-D scores of those with severe malocclusion differed significantly (p<0.001) from those with no or slight malocclusion. Construct validity showed significant association between the PIDAQ subscales with ranking of perceived dental appearance, need for braces and impact of malocclusion on daily activities. There were no floor or ceiling effects. Conclusion: The adapted English PIDAQ demonstrated adequate psychometric properties to be valid and reliable for assessment of psychological impacts of dental aesthetics among Malaysian adolescents.